2021
DOI: 10.3389/fimmu.2021.656908
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tumor Necrosis Factor in Manipulating the Immunological Response of Tumor Microenvironment

Abstract: The tumor microenvironment (TME) is an intricate system within solid neoplasms. In this review, we aim to provide an updated insight into the TME with a focus on the effects of tumor necrosis factor-α (TNF-α) on its various components and the use of TNF-α to improve the efficiency of drug delivery. The TME comprises the supporting structure of the tumor, such as its extracellular matrix and vasculature. In addition to cancer cells and cancer stem cells, the TME contains various other cell types, including peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 130 publications
0
63
1
1
Order By: Relevance
“…3 B). However, RNA-seq analysis of NFAT1 indicated that the expression of TNF, an activator of TNF signaling [ 24 ], was downregulated after NFAT1 silencing (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…3 B). However, RNA-seq analysis of NFAT1 indicated that the expression of TNF, an activator of TNF signaling [ 24 ], was downregulated after NFAT1 silencing (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…TNF-α plays a critical role in tumor signaling pathways and immune-cell manipulation within the TME.TNF-α induces diverse effects that are both oncogenic and tumor-suppressive [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other molecules directly connected to the central node were several pro-inflammatory molecules IL1B, IKK, IKB, and ERBB2. Oncogenic TGF-β signaling has been linked to PCa; nevertheless, a signature of TGF-β-regulated ECM genes has been identified in many CAFs and associated with poor prognosis [ 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%